Peningkatan Kesehatan Masyarakat dengan Pembuatan Cairan Fermentasi dari Limbah Sayur dan Buah sebagai Obat Kumur dan Obat Aneka Luka - Fahma Riyanti; Desnelli, Desnelli; Nova Yuliasari; Fatma, Fatma; Julinar, Julinar (Yayasan Literasi Sains Indonesia, 2024)
The liquid product resulting from fermentation of leftover vegetables and fruit that is still fresh and not rotten for approximately 100 days has the characteristics of being brown in color, has an aroma like vinegar or fresh sourness and a very acidic pH, namely less than 4. This fermented product contains acertic acid and lactic acid and is a natural antimicrobial source, so it has antibacterial and anti-fungal capabilities. This antibacterial activity can inhibit the activity of bacteria that cause tooth decay such as L.acidophilus and S.mutans bacteria so it can be used as a mouthwash. The wound healing process can be accelerated due to the presence of antibacterial compounds by stimulating the body's immune response. So that this fermented liquid can be used as a wound medicine. Community service activities in the form of counseling, practice of making fermented liquid and providing ready-made products are topics carried out at RT 07 LK IV, Timbangan Indralaya Utara, Ogan Ilir Sumatera Sealatan. The counseling participants were mothers and young women, estimated to be 15 - 25 people. To make it easier for the extension participants to understand and the aim of the activity to be achieved, a demonstration was carried out on making fermentation liquid, harvesting F2 products with mint leaves for gargling and distributing the product. The extension participants were very enthusiastic about participating in the activity, seen from the many questions asked.